2013
DOI: 10.1016/j.bbamem.2013.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the mouse ClC-K1/Barttin chloride channel

Abstract: Several Cl(-) channels have been described in the native renal tubule, but their correspondence with ClC-K1 and ClC-K2 channels (orthologs of human ClC-Ka and ClC-Kb), which play a major role in transcellular Cl(-) absorption in the kidney, has yet to be established. This is partly because investigation of heterologous expression has involved rat or human ClC-K models, whereas characterization of the native renal tubule has been done in mice. Here, we investigate the electrophysiological properties of mouse Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 40 publications
3
41
0
Order By: Relevance
“…The rodent CLC-K isoform rClC-K1 is active also in the absence of barttin and exhibits fast protopore and slow common gating steps. Co-expression of rClC-K1 and barttin results in a permanently open common gate (27,45). Although such effect on the common gate of human CLC-K channel function cannot be directly demonstrated, we recently demonstrated that hClC-Ka/barttin channels exhibit an open common gate (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rodent CLC-K isoform rClC-K1 is active also in the absence of barttin and exhibits fast protopore and slow common gating steps. Co-expression of rClC-K1 and barttin results in a permanently open common gate (27,45). Although such effect on the common gate of human CLC-K channel function cannot be directly demonstrated, we recently demonstrated that hClC-Ka/barttin channels exhibit an open common gate (27).…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast to hClC-Ka and hClC-Kb, rClC-K1 can form functional channels also in the absence of barttin (4,6,7). This property permits studying the effects of barttin on rClC-K1 gating and allowed identification of mechanisms underlying the functional CLC-K modification by barttin (27,45). We decided to use rClC-K1 carrying the V166E mutation to characterize the effects of carboxyl-terminal truncations on CLC-K function.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent mutations of the 'gating glutamate' in ClC-0 (Dutzler et al 2003) and CLC exchangers (Leisle et al 2011;Neagoe et al 2010) similarly largely abolished the voltage-dependence of currents. However, channels lacking this glutamate still gate at the single-channel level (Dutzler et al 2003;L'Hoste et al 2013), indicating that CLC gating cannot be explained entirely by the movement of its side chain. Voltage-gating of CLC channels depends on the Cl − concentration.…”
mentioning
confidence: 99%
“…(mClC-K1 and mClC-K2) (4), and humans (hClC-Ka and hClC-Kb) (5) and have been shown to be essential for sensory transduction in the inner ear and for normal urinary concentration. They mediate Cl Ϫ efflux in the thin ascending limb (ClC-K1/ClC-Ka; Refs.…”
mentioning
confidence: 99%